Dakwah Transformatif Melalui Pendekatan Kultural pada Kalangan Remaja : (Studi Majelis Khoirun Dakwah Probolinggo) - Kurniawan Ramadhani; Baidawi (Jisab, 2023)
Various forms immoral behavior still color lines people's lives, such as phenomenon teenagers wearing earrings, piercings, and gold necklaces. A number factors behind, namely unhealthy environment and wrong associations make younger generation trapped in dishonorable acts. This spiritual dryness is of course concern a number da'wah activists in context embracing young people back on right path in order to gain God's approval. Khoirun Dakwah Assembly is here as an effort to galvanize morals of younger generation through various positive activities and cultural approaches. Transformative da'wah based on a cultural approach is expected to be able to create social change in society. Therefore, this study uses a qualitative-descriptive research method with a phenomenological type research. That in qualitative research is research through research procedures produce descriptive data. Results this study are 1). Activity of reciting blessings every Friday night involves teenagers led directly by Habib Achmad Zaqik Al-Hasni 2). Forming an ontel community in galvanizing morals youth towards productive activities through cultural approach. 3) The Khoirun Da'wah Assembly held an ajangsana with Kerpangan residents. 4). Providing compensation for orphans and widows as well as the poor as a form of concern for others.